Design and construction of adaptive clothing for selected children with cerebral palsy - Malvar, Astrud Quinton; Lumawig, Maria Josephine T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2011)
ABSTRACT Specialized functional is needed to address different garment concerns experienced by a child with cerebral palsy to ensure that the child's full potential is attained. The study aimed to answer what design features should be incorporated in adaptive clothing to address the specific clothing needs of a child with cerebral palsy, with the objective of designing and constructing adaptive clothing for them. The study utilized the multiple case study method on three (3) children, ages four to ten years old, who are currently undergoing therapy at the Philippine Children's Medical Center. Through observations and interviews, factors to consider in designing adaptive clothing, such as mobility skills and difficulties encountered with ready to wear clothing were gathered. Adaptive clothing designs were developed with the objective of promoting independence in dressing and providing assistanceto the guardians. These designs were constructed and tested for ease in wearing, comfort and movement. Follow-up interviews showed that the garments designed were able to realize the set objectives. The solutions incorporated focused on the use of alternative garment opening locations and accessories which were simple in terms of operation. One design developed had garment openings on each shoulder and at the front, which provided ease to the guardian and wearer by allowing dressing in a lying down position. Through adaptations in clothing, independence in dressing was realized and assistance through ease of wearing was provided for both guardian and subject. The study can be further improved by including a week-long garment testing period for more observations.
Thesis (Bachelor of Science in Clothing Technology)--University of the Philippines Diliman.
Keywords: Children's clothing -- Pattern design; Cerebral palsied children -- Clothing